Pengaruh HEBI (Health Educational Based Intervention) Terhadap Kesiapsiagaan Bencana Rumah Tangga - Rasyida, Zulfa Mahdiatur; Yani, Laras Putri; Husain, Mohammad Achnaf Hadyan Al (Maternal & Neonatal Health Journal, 2024)
Patient knowledge is very influential in therapy for people with diabetes mellitus. Diabetes mellitus is a chronic condition in which there is an increase in glucose levels in the blood because the body cannot produce insulin effectively. The purpose of this study was to determine the effect of providing educational videos about diabetes mellitus on the level of knowledge in type 2 diabetes mellitus patients at Chania Care Center. This research design is pre-experimental with a one group pre and post-test design approach. The sampling using total sampling technique with a large population of diabetics obtained a sample of 30 respondents. The independent variable is educational videos while the dependent variable is knowledge level.Using questionnaire instruments. Using the Paired T-Test with a level of significance (?:0.05). The results showed that 21 respondents had less knowledge before giving the video to 5 respondents after giving the video. Respondents with sufficient knowledge amounted to 4 to 14 respondents. The amount of good knowledge increased from 5 respondents to 11 respondents out of a total of 30 respondents. The results of the analysis of the Paired T- Test showed that the influence of 6-9 p value = 0.000 < ? = 0.5 H1 was accepted. In conclusion, there is an effect of providing educational videos about diabetes mellitus on the level of knowledge in type 2 diabetes mellitus patients. Interesting educational videos will be easily understood by many people and often the intensity of learning will increase one's knowledge and understanding. Diabetes educational videos can be used as promotional media to increase diabetes knowledge.